Thyroid Cell Differentiation from Murine Induced Pluripotent Stem Cells - Ma, Risheng; Morshed, Syed A.; Latif, Rauf; Davies, Terry F. (Frontiers in Endocrinology, 2015)
Background: Here we demonstrate the successful differentiation of induced pluripotent stem (iPS) cells into functional thyroid cells indicating the therapeutic potential of this approach when applied to individuals with thyroid deficiency. Research Design and Methods: Using embryonic murine fibroblasts we generated iPS cells with a single lentiviral “stem cell cassette” (STEMCCA) vector and then differentiated these IPS cells into thyroid cells after transfection with PAX8 and NKX2-1 by Activin A and TSH stimulation. Results: The generated iPS cells expressed pluripotent stem cell markers as assessed using both reverse transcription quantitative PCRs (RT-qPCR) and Immunofluorescence staining with approximately 0.5% reprogramming efficiency. Compared to control cells, the expression of thyroid specific genes NIS, TSHR, Tg and TPO were greatly enhanced in PAX8+NKX2-1+ iPS cells after differentiation. On stimulation with TSH these differentiated iPS cells were also capable of dose-dependent cAMP generation and radioiodine uptake indicative of functional thyroid epithelial cells. Furthermore, the cells formed three-dimensional follicles in culture, and “thyroid organoids” formed after PAX8+NKX2-1+ iPS cells transplanted into nude mice, and all expressed Tg protein as judged immnohistochemically. Taken together, thyroid epithelial cells differentiated from iPS cells which were themselves derived from murine fibroblasts exhibited very similar properties to thyroid cells previously developed from traditional murine embryonic stem cells. Conclusion: Thyroid cells differentiated from IPS cells offer the opportunity to examine the detailed transcriptional regulation of thyroid cell differentiation and may provide a useful future source for individualized regenerative cell therapy.